2016
DOI: 10.1038/srep18726
|View full text |Cite
|
Sign up to set email alerts
|

Amy63, a novel type of marine bacterial multifunctional enzyme possessing amylase, agarase and carrageenase activities

Abstract: A multifunctional enzyme is one that performs multiple physiological functions, thus benefiting the organism. Characterization of multifunctional enzymes is important for researchers to understand how organisms adapt to different environmental challenges. In the present study, we report the discovery of a novel multifunctional enzyme Amy63 produced by marine bacterium Vibrio alginolyticus 63. Remarkably, Amy63 possesses amylase, agarase and carrageenase activities. Amy63 is a substrate promiscuous α-amylase, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…For example, the multifunctional amylase Amy440 produced by Aquimarina agarilytica ZC1 was reported to show amylase and agarase activities (Lin et al 2017); the multifunctional amylase Amy63 produced by Vibrio alginolyticus 63 was reported to show amylase, agarase. and carrageenase activities (Liu et al 2016); and the multifunctional amylase Amy19 produced by Bacillus BI-19 was reported to show agarase, carrageenase, and cellulase activities (Li et al 2019). To the best of our knowledge, Amy2587 is the rst multifunctional enzyme found to have ve enzyme activities at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the multifunctional amylase Amy440 produced by Aquimarina agarilytica ZC1 was reported to show amylase and agarase activities (Lin et al 2017); the multifunctional amylase Amy63 produced by Vibrio alginolyticus 63 was reported to show amylase, agarase. and carrageenase activities (Liu et al 2016); and the multifunctional amylase Amy19 produced by Bacillus BI-19 was reported to show agarase, carrageenase, and cellulase activities (Li et al 2019). To the best of our knowledge, Amy2587 is the rst multifunctional enzyme found to have ve enzyme activities at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, enzymes were believed to have high selectivity or speci city for their substrates and reactions (Dan 2020). However, enzymes with cross-reactivity or promiscuity have been discovered and characterized (Liu et al 2016; Khersonsky et al 2006;Pocker and Stone 1965), and increasing numbers of multifunctional enzymes that can hydrolyze various substrates to produce oligosaccharides have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…OT37‐5b. The procedure was carried out as described previously with minor modification (Liu et al ., 2016). The bismuth strained proteins were manually excised from the gel and digested with trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Directly using the supernatant of fermentation broth containing agarase without protein purification is an effective method to save these costs, although rare relevant works are reported until now. Moreover, crude agar and agarose were used as the substrates to produce the oligosaccharides in these previous studies , thereby increasing the cost of industrial production. In our previous work , a GH16 β‐agarase gene, agaM1 (GenBank accession number: MG280837), was expressed in E. coli cells and was further purified for enzymatic assays.…”
Section: Introductionmentioning
confidence: 99%